Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $\{\epsilon_n\}$ be a sequence where $\epsilon_n$ is either $ 1$ or $-1$. How could I Show
that the sum of the series


is an irrational number.

share|cite|improve this question
Just repeat the arguments in the regular proof that e is irrational. – achille hui May 9 '13 at 15:17
As a matter of fact, using the proof/arguments listed below, we can generalize the result further. As long as $\epsilon_n \in \{-1,1\}$ comes in infinite quantities, you can allow some (even if infinite) $\epsilon_n$ be 0. That is, $\epsilon_n \in \{-1,0,1\}$. You simply cannot have a finite number of both $-1,1$. – CogitoErgoCogitoSum Nov 29 '14 at 1:16

If there exist $p\in\mathbb{Z}$ and $q\in\mathbb{N}$, such that $\frac{p}{q}=\sum_{n=0}^\infty\frac{\epsilon_n}{n!}$, then $q!\cdot\sum_{n=q+1}^\infty\frac{\epsilon_n}{n!}$ must be an integer. However, $$|q!\cdot\sum_{n=q+1}^\infty\frac{\epsilon_n}{n!}-\frac{\epsilon_{q+1}}{q+1}|\le\sum_{n=q+2}\frac{q!}{n!}<\frac{1}{(q+1)(q+2)}\cdot\sum_{m=0}\frac{1}{2^m}=\frac{2}{(q+1)(q+2)},$$ which implies that $$0<\frac{1}{q+1}-\frac{2}{(q+1)(q+2)}\le |q!\cdot\sum_{n=q+1}^\infty\frac{\epsilon_n}{n!}|\le \frac{1}{q+1}+\frac{2}{(q+1)(q+2)}<1,$$ a contradiction.

share|cite|improve this answer

The proof is by contradiction. Define: $$ S = \sum_{k \ge 0} \frac{\epsilon_k}{n!} $$ Assume $S$ is rational, i.e. there are $u \in \mathbb{Z}$, $v \in \mathbb{N}$ such that $S = u / v$.

Pick $b > v$, so that $b \ge 2$. Then $b! S$ is an integer, i.e.: $$ S = \sum_{0 \le k \le b} \frac{b! \epsilon_k}{k!} + \sum_{k > b} \frac{b! \epsilon_k}{k!} $$ The first sum is an integer, so the second sum has to be an integer too. Now: $$ \frac{b! \epsilon_k}{k!} = \frac{\epsilon_k}{(b + 1) (b + 2) \ldots k} $$ But: $$ \frac{1}{(b + 1) (b + 2) \ldots k} < \frac{1}{b^{k - b}} $$ By the triangular inequality: $$ \left\rvert \sum_{k \ge b + 1} \frac{b! \epsilon_k}{k!} \right\rvert \le \sum_{k \ge b + 1} \frac{b!}{k!} < \sum_{k \ge b + 1} b^{-k} = b^{- b - 1} \sum_{k \ge 0} b^{-k} = b^{- b - 1} \frac{1}{1 - 1 / b} = \frac{1}{b^{b +1} (b - 1)} < \frac{1}{b^{b + 1}} $$ So: $$ 1 = \left\lvert \frac{b! \epsilon_b}{b!} \right\rvert > \left\rvert \sum_{k \ge b + 1} \frac{b! \epsilon_k}{k!} \right\rvert $$ and the "leftover sum" can never be 0, so it isn't an integer.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.